Menakar Transparansi Keuangan Partai Politik Pada Pelaksanaan Pemilihan Umum - Arfiani, Arfiani; Syofyan, Syofirman (Nagari Law Review, 2023)
To support the implementation of the implementation of political party activities cannot be separated from the existence of large financial support. In the process of traveling political parties, political party funds come from contributions from party politicians, legitimate contributions in accordance with legal provisions; as well as financial assistance from the APBN and APBD from the government. Through the funds generated, an accountable and transparent report is needed to the public in order to create legal certainty and prevent acts of corruption originating from the party's funds. So through this research the authors underline the 2 (two) formulation of the problem that is important to be discussed. First, what is the urgency of disclosing political party financial information in preventing cultural practices of corruption in Indonesia? And Second, how is the accountability of political party financial funds sourced from APBN and APBD funds in Indonesia? This research uses the type of normative juridical research. The data used in the research comes from primary legal materials, secondary legal materials and literature studies from various literatures. The results of this study note that the form of political party financial reporting must record all sources of receipt of funds for the party and not only be accountable for funds originating from the APBN and APBD, then with regard to sanctions there must be strict action taken by the government not only the imposition of administrative sanctions imposed against a party.